Vascular Reactivity to Hypercapnia Is Impaired in the Cerebral and Retinal Vasculature in the Acute Phase After Experimental Subarachnoid Hemorrhage - Warner, Laura; Bach-Hagemann, Annika; Albanna, Walid; Clusmann, Hans; Schubert, Gerrit A.; Lindauer, Ute; Conzen-Dilger, Catharina (Frontiers in Neurology, 2022)
Objective: Impaired cerebral blood flow (CBF) regulation such as reduced reactivity to hypercapnia contributes to the pathophysiology after aneurysmal subarachnoid hemorrhage (SAH), but temporal dynamics in the acute phase are unknown. Featuring comparable molecular regulation mechanisms, the retinal vessels participate in chronic and subacute stroke- and SAH-associated vessel alterations in patients and can be studied non-invasively. This study aims to characterize the temporal course of the cerebral and retinal vascular reactivity to hypercapnia in the acute phase after experimental SAH and compares the potential degree of impairment. Methods: SAH was induced by injecting 0.5mL of heparinized autologous blood into the cisterna magna of male Wistar rats using two anesthesia protocols (isoflurane/fentanyl n= 25 (Sham + SAH): Iso - Group, ketamine/xylazine n= 32 (Sham + SAH): K/X - Group). CBF (laser speckle contrast analysis) and physiological parameters were measured continuously for 6h. At six predefined time points, hypercapnia was induced by hypoventilation controlled via blood gas analysis and retinal vessel diameter (RVD) was determined non-invasively. Results: Cerebral and retinal reactivity in sham groups were stable with only a slight attenuation after 2 hours in RVD of the K/X - Group. In the SAH Iso - Group, cerebral and retinal CO2 reactivity compared to baseline was immediately impaired starting at 30min after SAH (CBF p=0.0090, RVD p=0.0135) and lasting up to 4h (p=0.0136, resp. p=0.0263). Likewise, in the K/X - Group, cerebral CO2 reactivity was disturbed early after SAH (30min p=0.003) albeit showing a recovery to baseline after 2h while retinal CO2 reactivity was impaired over the whole observation period (360min p=0.0001) in the K/X - Group. After normalization to baseline, both vascular beds showed a parallel behavior regarding temporal course and extent of impairment. Conclusion: This study provides a detailed temporal analysis of impaired cerebral vascular CO2 reactivity starting immediately after SAH and lasting up to 6h. Importantly, the retinal vessels participate in these acute changes underscoring the promising role of the retina as a potential non- invasive screening tool after SAH. Further studies will be required to determine the correlation with functional outcome.